2009
DOI: 10.1160/th09-01-0061
|View full text |Cite
|
Sign up to set email alerts
|

Binding between heparin and the integrin VLA-4

Abstract: SummaryHeparin possesses antimetastatic effects that were related to various molecular mechanisms beyond anticoagulant activities. The ability of heparin to interfere with the function of adhesion receptors in the metastatic course appears as a promising therapeutic approach. This refers to numerous findings that heparin attenuates metastasis in a selectin-dependent manner. We recently demonstrated that heparin interferes with the integrin VLA-4 on murine melanoma cells binding to VCAM-1. To confirm this activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
3
23
0
2
Order By: Relevance
“…In fact, previous studies, performed with radioactive or fluorescent heparin derivatives showed that these compounds were bound and internalized by SMC (20), human endothelial cells (21) and rat neurons (33). Other reports show that heparin binds to specific cell surface adhesion molecules, for example, integrins to modulate the adhesive capabilities of different cell lines (34,35). The present study clearly demonstrates that M5 melanoma cells uptake heparin which results in its cytoplasmic and nuclear localization.…”
Section: Discussionsupporting
confidence: 73%
“…In fact, previous studies, performed with radioactive or fluorescent heparin derivatives showed that these compounds were bound and internalized by SMC (20), human endothelial cells (21) and rat neurons (33). Other reports show that heparin binds to specific cell surface adhesion molecules, for example, integrins to modulate the adhesive capabilities of different cell lines (34,35). The present study clearly demonstrates that M5 melanoma cells uptake heparin which results in its cytoplasmic and nuclear localization.…”
Section: Discussionsupporting
confidence: 73%
“…Such an activity is reported by Schlesinger et al (7) who demonstrate that the low-molecular-weight heparin (LMWH) tinzaparin interferes with integrin α4β1/VLA-4 binding to its counter-receptor vascular cell adhesion molecule-1 (VCAM-1). They used an acoustic wave biosensor to analyse these interactions.…”
Section: Anticoagulant and Non-anticoagulant Functions Of Glycosaminomentioning
confidence: 74%
“…Although we described numerous structure-activity relationships of heparin-VLA-4 binding [36] the relevance of this interaction has never been addressed in vivo. Here we show that VLA-4 on murine melanoma cell line B16F10 contributes dominantly to its experimental metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of B16F10 and B16F10-VLA-4kd cells with the ligand VCAM-1 was investigated under physiological flow conditions in a parallel plate flow chamber as described before [35,36]. Briefly, VCAM-1 Fc chimera (0.2 μg) was coated on glass slides which were incorporated into a parallel plate flow chamber and mounted on an inverted microscope.…”
Section: Flow Chamber Assaymentioning
confidence: 99%